Histology and Histomorphometry of The Skin of Gallus gallus domesticus, Anas platyrhynchos and Columba livia on The Caudal Region - Masyitha, Dian; Zainuddin, Zainuddin; Iskandar, Cut Dahlia; Rahmi, Erdiansyah; Sayuti, Arman; Nursalim, M; Ningrum, Aulia Putri Wahyu (Serambi Saintia : Jurnal Sains dan Aplikasi, 2023)
The skin is an organ that functions to coat, protect and wrap the surface of the body and can maintain the balance of fluids in the body, including in birds. Aves skin can also provide a thermal insulation function. In general, the skin layers of aves consist of the epidermis, dermis and hypodermis. This study aimed to describe the histological structure and histomorphometric skin of native chickens (Gallus gallus domesticus), ducks (Anas platyrhynchos) and pigeons (Columba livia) in the caudal region. The samples used were six individuals each of. The skin of the caudal region of the sample is then processed, started from preparation to a histological preparation with a thickness of 5 m, followed by Haematoxylin-Eosin (HE) staining. The results showed that the histological structure of the skin of the three types of aves consisted of the epidermis, dermis and hypodermis with a thinner thickness than the skin of mammals. The measured histomorphometric data showed that the epidermal layer thickness of the skin of the caudal region of native chickens, ducks and pigeons was not significantly different (P0.05), there was a significant difference (P0.05) in the thickness of the dermis and hypodermis layers. It was concluded there was no difference in the histological structure of the skin of native chickens, ducks and pigeons, the skin histomorphometry of the caudal region of native chickens, the dermis and hypodermis were thicker than those of ducks and pigeons.Keywords: Skin, aves, caudal, histology, histomorphometry.